Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2015
DOI: 10.1177/1078345815572347
|View full text |Cite
|
Sign up to set email alerts
|

HIV/AIDS Research in Correctional Settings

Abstract: Housing a large number of individuals living with or at risk for HIV/AIDS, correctional settings have considerable potential for epidemiological, prevention, and treatment research. However, federal regulations and institutional challenges have limited the extent and types of such research with prisoners. This study examines the degree to which HIV/AIDS correctional researchers report greater challenges than do their non-correctional counterparts. Results indicated that correctional researchers reported signif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
14
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 26 publications
(41 reference statements)
0
14
0
Order By: Relevance
“…Are researchers who have worked in correctional settings burned out by the challenges of doing correctional work, so that they cannot begin to fathom yet one more stakeholder groups that needs to be satisfied and heard? Our prior work has shown that research in correctional settings presents unique challenges and barriers (Eldridge et al, 2012;Eldridge, Johnson, Brems, & Corey, 2011;Johnson et al, 2014Johnson et al, , 2015. .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Are researchers who have worked in correctional settings burned out by the challenges of doing correctional work, so that they cannot begin to fathom yet one more stakeholder groups that needs to be satisfied and heard? Our prior work has shown that research in correctional settings presents unique challenges and barriers (Eldridge et al, 2012;Eldridge, Johnson, Brems, & Corey, 2011;Johnson et al, 2014Johnson et al, , 2015. .…”
Section: Discussionmentioning
confidence: 99%
“…Because of the stringent safeguards consequent to the Holmesburg and other prison studies, research in prisons has become somewhat arduous and time consuming. These difficulties, combined with unique institutional challenges, including restrictions on prisoners’ movements, emphasis on security, and closed nature, present formidable obstacles to conducting research in correctional settings (Johnson, Kondo, Brems, & Eldridge, 2015). As a result, although valuable research is being conducted in prison settings around the world focusing on a wide range of issues and using a variety of methodological approaches, the scope and amount of health-related research is considerably underwhelming when the extent of the health challenges faced by prisoners is considered.…”
mentioning
confidence: 99%
“…Recent findings (Johnson et al, in press) revealed that researchers who conduct HIV/AIDS research in correctional settings reported experiencing significantly more frequent challenges than researchers who conduct HIV/AIDS research in non-correctional settings and that the challenges were particularly related to the nature of the research setting (e.g., navigating policies and procedures, access to participants, obtaining research review and approval, incentives and compensation). These findings are consistent with the fact that participants with correctional experience identified a larger number of training topics.…”
Section: Discussionmentioning
confidence: 99%
“…We have previously highlighted the paucity of knowledge of federal regulations for protections of prisoners as research participants (Johnson et al, 2014) and ethical challenges related to research in correctional settings (Eldridge et al, 2012; Johnson et al, in press). The findings reported here expand our prior reports by identifying the specific areas of training desired.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation